Modelling of just-in-time distrubution network under raw material quality and time constraints - Gursoy, Beren; Soner Kara, Selin (YILDIZ TECHNICAL UNIV, 2021)
Just-in-time (JIT) delivery is one of the key delivery strategies that enable the right quality product to reach the point of demand at the right time without creating unnecessary costs in the supply chain network. The concepts of quality and time are two main factors to be considered in this issue. Particularly because the variability in quality directly affects cost and time, it is very important for JIT delivery. In this study, the effect of raw material quality within the supply chain network which tries to ensure JIT delivery is examined. For this, a multi-stage, multi-period mixed-integer mathematical model is proposed in the study. The model aims to minimize the total supply chain cost by trying to balance the purchasing and quality costs for manufacturers. In addition to standard constraints, the stock balance and time constraints have been developed for JIT delivery. As a result of the model resolved with the GAMS Distribution 21.6 program, 34.5% of the raw material supplied from suppliers is provided from 1st quality raw materials, while 65.5% is provided from 2nd quality raw materials. Despite its low purchasing costs, 3rd quality raw material has not been preferred by the producers in any period because it causes a delay in JIT delivery. Besides, it is seen that deliveries are made very close to the maximum delivery time of distribution centers, depending on the variability in raw material quality. It is understood that raw material quality is an important concept in a JIT supply chain network due to its significant impact on time.
Keywords: Supply chain network desing; JIT; Quality; Lead time; MILP; GENETIC ALGORITHM; LOGISTICS; Engineering